Review on foreign body in rumen and reticulum of ruminants - Tolesa Neggasa (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Cattle play significant contribution in Ethiopian economy as source of meat, milk, drought power, income and foreign exchange. Gastrointestinal foreign bodies are among the most common surgical emergency in veterinary medicine. Swallowed metallic object such as nails or piece of wires, fall directly into the reticulum or pass in to the rumen and are subsequently carried over the rumen reticular folds into the carnio-ventral part of the reticulum. Cattle are more likely to ingest foreign bodies than small ruminant since they don’t use their lips for prehension and are more likely to eat a chopped feed. The condition is more common during drought because animals are grazing closer to the ground. The object can penetrate the diaphragm and enter the thoracic cavity causing pleuritis. Metal detectors were used at one time to aid in the diagnosis of traumatic reticuloperitonitis. Ferrous metallic foreign bodies can be detected with metal detectors. Foreign bodies have great economic significance associated with reduced production and productivity of animals suffering from them.